MODELING AND CAM SIMULATION FOR MANUFACTURING OF 3D SHROUDED IMPELLER USED IN CENTRIFUGAL COMPRESSOR (Journal of Manufacturing Engineering, 2018)
Impeller is the most fundamental component of any turbo machinery, the complexity of its design varies from application point of view. Design and manufacturing of such components is a research interest with varying difficulty in the component geometries with complexity and between ranges of materials. To accomplish such complex task engineers need knowledge of design for manufacturing kind of tools which equips latest processes like scoop milling technology. To implement such new technologies one needs a pre planning right yet from design phase. To accommodate such complications in design phase tools like NXCAD and NXCAM modules has been used for modelling and tool path generation which is used to simulate manufacturing of a 3D shrouded impeller used in centrifugal compressor to alter the flow of fluids (gasses/ liquids). A three dimensional shrouded impeller has been modelled using NX CAD and tool path has been generated in view to simulate the manufacturing profiles of scoop milling process with the guided programmable pre and post processing by using NX CAM. By using this simulation, manufacturing of parts produced by CNC machine in computer can be virtually simulated which provides error free manufacturing of impeller from block to functional part.
Keywords: 3D shrouded Impeller of centrifugal compressor; NX CAD/CAM; CNC simulation